PENGARUH GAYA HIDUP TERHADAP KENAIKAN TEKANAN DARAH DI KOTA SEMARANG - Prasetyaningrum, Erna; Suharsanti, Ririn (Media Farmasi Indonesia, 2017)
ABSTRACT One of the degenerative diseases causing death was cardiovascular diseases. Hypertension is a major risk factor for cardiovascular found in 14% of the Indonesian population. Many risk factors that cause hypertension are lifestyle habits such as smoking, drinking alcohol, fatty foods. The aim of research is to know the correlation between the lifestyle of the community blood pressure rise in Semarang. Research is a non-experimental research. The variables studied are gender, age, smoking behavior, relish eating fried foods, offal, fat, drinking sodas and coffee. The research subject is Jatisari village community Mijen Subdistrict, District Limbangan boja and Muktiharjo Tlogosari Semarang. The number of subjects are 54 people, at least 20 years old. Collecting data is carried out using interview techniques and measurement of blood is performed pressure using a sphygmomanometer. Data were analyzed by descriptive analytic. The results showed that increased blood pressure in people Semarang based on gender male by 29.6%, amounting to 70.4% of women, by the age of 20-30 years was 1.8%, 30-40 th of 3.7 %, 7.5% 40-50 years old, 50-60 years old 31.5%, 60-70 years old amounted to 35.2%,> 70 th by 20.4%, amounting to 20.7% of smoking, eating fries 44.6%, eating offal of 5.4%, 11.9% fat meal, drink soft drinks by 3.3%, coffee by 20.7%, 6.5% high-salt foods. The education related to the symptoms, risk factors, treatment of hypertension and prevention of complications through printed and electronic media can prevent hypertension or other complications.